2022
DOI: 10.3390/agronomy12071484
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Production System (Organic versus Conventional) on Olive Fruit and Oil Yields and Oil Quality Parameters in the Messara Valley, Crete, Greece; Results from a 3-Year Farm Survey

Abstract: The demand for organic olive oil has increased rapidly over the last 40 years, but there is limited information on the effects of organic production methods on commercially and nutritionally relevant quality parameters in olive oil. The main objective of this farm survey-based study was therefore to compare fruit and oil yields and important oil quality parameters (including acidity, peroxide value and fatty acid profiles) between organic and conventional farms located in the Messara Plain and foothills. As ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 43 publications
(75 reference statements)
1
12
1
Order By: Relevance
“…The finding that olive yields of the table olive variety 'Kalamon' in plots with vetch cover crops were not significantly different to those recorded in Medicago plots (which had a very low Medicago plant density and can be considered a no-cover crop control treatment) was therefore not surprising. It is important to note that fruit yields of the variety Koroneki (which is the dominant variety used for olive oil production in Crete) were reported to be not significantly different, in fact numerically ~10% higher, in organic compared with conventionally managed fields in the Messara region [4,28].…”
Section: Effect Of Different Cover Crop Treatments On Crop Performancementioning
confidence: 99%
“…The finding that olive yields of the table olive variety 'Kalamon' in plots with vetch cover crops were not significantly different to those recorded in Medicago plots (which had a very low Medicago plant density and can be considered a no-cover crop control treatment) was therefore not surprising. It is important to note that fruit yields of the variety Koroneki (which is the dominant variety used for olive oil production in Crete) were reported to be not significantly different, in fact numerically ~10% higher, in organic compared with conventionally managed fields in the Messara region [4,28].…”
Section: Effect Of Different Cover Crop Treatments On Crop Performancementioning
confidence: 99%
“…A randomised block design was used incorporating four blocks of 48 Kalamon olive trees, each split into four treatment plots (12 trees/plot). In treatment plots, four different cover crop treatments were applied for three consecutive growing seasons (2005/2006, 2006/2007 and 2007/2008) to compare their effect of cover crops on (a) invertebrate activity (results reported in this article), and (b) Oxalis (Oxalis pes-caprae L.) establishment, olive yields, mineral supply to olive trees and olive fly infestation [7,18]. The four cover crop treatments were: (i) Vetch (Vicia sativa L.) without Rhizobium inoculation, (ii) a mixture of vetch (Vicia sativa L.), pea (Pisum sativum L.) and barley (Hordeum vulgare L.), (iii) Vetch (Vicia sativa L.) with Rhizobium inoculation (Legume Fix, Legume Technology Ltd., Nottinghamshire, UK) and (iv) a native wild Medicago species (Medicago polymorpha L.).…”
Section: Experimental Design Of the Cover Crop Comparison Trialmentioning
confidence: 99%
“…Organic farming systems prohibit the use of all synthetic chemical pesticides, although some insecticides made from plant extracts (e.g., pyrethrum) or microbial fermentation (Spinosad) are permitted [17]. However, although Spinosad is permitted, it is not thought to be widely used in organic production, due to its relatively high cost and the availability of efficient mass-trapping systems [1,18,19]. These baited traps, which contain food, colour and/or pheromone attractants and a lethal agent (e.g., an insecticide), are placed throughout an orchard prior to fruit setting and have been shown to be as effective as pesticide sprays in reducing fly numbers and fruit infestation, especially in Mediterranean regions with relatively low olive fly pest pressure [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1252 (2023) 012161 IOP Publishing doi:10.1088/1755-1315/1252/1/012161 2 Some treatments of foliar spray and ground fertilizer may not be suitable due to the presence of a non-significant and sometimes negative effect on productivity indicators such as the weight of the fruit, the recent shoot length, the oil content of fatty acids and polyphenols, so it is necessary to continue searching until reach the appropriate concentration [5]. Some studies indicated that there is no significant difference in the fatty acid composition of olive oil according to the production systems, and this itself is a result [6,7], but the pursuit continues through research to reach a better content of desirable fatty acids such as oleic acid by using fertilizers that are compatible with the organic production system. This present research aimed to evaluate the effect of certified organic fertilizer in olive oil quality to adjust the quantity and optimal method of addition to get the best result.…”
mentioning
confidence: 99%